Relativizzare la via per non relativizzare la meta? La bellezza a partire dal dibattito filosofico angloamericano contemporaneo (Lebenswelt. Aesthetics and philosophy of experience., 2018)
The article: 1. analyzes the Anglo-American philosophical works which, in the last thirty years, focus on the notion of beauty by making reference to Kant’s work (in particular, Beauty restored by Mary Mothersill, Only a promise of happiness: the place of beauty in a world of art by Alexander Nehamas and Beauty by Roger Scruton); 2. argues that choosing Kant’s work means choosing a strategy which opens to a notion of beauty which is relative, but not relativistic, subjective, but not anarchic, that is, universal, but not absolute; 3. argues that the most powerful tool Kant introduces to make it possible relativizing the way (i.e., the form of beauty in a given space and in a given time) not to relativize the aim (i.e., the meaning of beauty, which is actually quite stable in the history of Western culture) may be his notion of ideal (which is almost ignored in the contemporary Anglo-American philosophical works), since it includes, and does not exclude, the most relative, particular and variable cases in its very genesis.